Community-Level Vulnerabilities and Political Field Experiments - Evans, Cara (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2022)
Most research ethics literature on vulnerability focuses on the vulnerability of individuals and populations defined by the potential vulnerability of their members (such as adults with intellectual disabilities or prisoners). However, research involving human participants does not always take the individual as the unit of analysis: political experiments may apply an intervention to a community as a whole. This paper argues that community-level vulnerability is not reducible to the sum of the vulnerabilities of community members, and that there is thus a need to consider vulnerability at the community level of analysis when analyzing the ethical implications of political field experiments. I first review ethical literature on community intervention research and the emerging scholarship on the ethics of political field experiments. I then highlight key accounts of the concept of vulnerability at an individual level. Drawing on Whitfield’s concept of “collective wrongs,” I argue that communities can be negatively affected in ways that are distinct from harms to individual community members, and that variation in susceptibility to such wrongs at the community level is largely consistent with existing conceptualizations of vulnerability. I suggest questions that researchers should consider when designing political field experiments to ensure that community-level vulnerabilities are taken into account.